Meaningful values of the EQ-5D-3L in patients undergoing primary knee arthroplasty. Issue 9 (7th September 2022) - Yapp, Liam Z.; Scott, Chloe E. H.; Howie, Colin R.; MacDonald, Deborah J.; Simpson, A. Hamish R. W.; Clement, Nick D.
Abstract : Aims: The aim of this study was to report the meaningful values of the EuroQol five-dimension three-level questionnaire (EQ-5D-3L) and EuroQol visual analogue scale (EQ-VAS) in patients undergoing primary knee arthroplasty (KA). Methods: This is a retrospective study of patients undergoing primary KA for osteoarthritis in a university teaching hospital (Royal Infirmary of Edinburgh) (1 January 2013 to 31 December 2019). Pre- and postoperative (one-year) data were prospectively collected for 3, 181 patients (median age 69.9 years (interquartile range (IQR) 64.2 to 76.1); females, n = 1, 745 (54.9%); median BMI 30.1 kg/m 2 (IQR 26.6 to 34.2)). The reliability of the EQ-5D-3L was measured using Cronbach's alpha. Responsiveness was determined by calculating the anchor-based minimal clinically important difference (MCID), the minimal important change (MIC) (cohort and individual), the patient-acceptable symptom state (PASS) predictive of satisfaction, and the minimal detectable change at 90% confidence intervals (MDC-90). Results: The EQ-5D-3L demonstrated good internal consistency with an overall Cronbach alpha of 0.75 (preoperative) and 0.88 (postoperative), respectively. The MCID for the Index score was 0.085 (95% confidence interval (CI) 0.042 to 0.127) and EQ-VAS was 6.41 (95% CI 3.497 to 9.323). The MICCOHORT was 0.289 for the EQ-5D and 5.27 for the EQ-VAS. However, the MICINDIVIDUAL for both the EQ-5D-3L Index (0.105) and EQ-VAS (-1) demonstrated poor-to-acceptable reliability. The MDC-90 was 0.023 for the EQ-5D-3L Index and 1.0 for the EQ-VAS. The PASS for the postoperative EQ-5D-3L Index and EQ-VAS scores predictive of patient satisfaction were 0.708 and 77.0, respectively. Conclusion: The meaningful values of the EQ-5D-3L Index and EQ-VAS scores can be used to measure clinically relevant changes in health-related quality of life in patients undergoing primary KA. Cite this article: Bone Joint Res  2022;11(9):619–628.